Micro small medium business development strategy of bonaparte coffe house in Sidenreng Rappang Regency - Ardiansyach Ardiansyach; Djabir Hamzah; Nurdjannah Hamid (Institute of Computer Science (IOCS), 2023)
This study aims to examine the Bonaparte Coffe HOUSE (UMKM) development strategy. This study will then be able to have a positive impact on Bonaparte Cofee HOUSE Business Actors in the form of business evaluation and facilitate the determination of future development strategies.This research was conducted descriptively in Panca Rijang District, Sidenreng Rappang Regency, South Sulawesi Province by collecting two types of data, namely primary data and secondary data. The research was analyzed using the help of the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices to answer the strategic factors which are the strengths and weaknesses as well as opportunities and threats for UMKM. to formulate and set priorities for the MSME development strategy, a SWOT analysis is then carried out. The results of the study indicate that there are several strategies that can be used to develop UMKM Bonaparte Coffe HOUSE which include: Improving product quality and expanding market expansion, Provision of parking lots equipped with security technology.